2015
DOI: 10.1089/acm.2015.0156
|View full text |Cite
|
Sign up to set email alerts
|

Online Education for Improving Communication and Documentation of Dietary Supplements Among Health Professionals Practicing in a Hospital Setting

Abstract: An online curriculum is an effective tool for presenting DS education to clinicians with the goal of improving clinicians' knowledge, confidence, and documentation practices about DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…Internet CME courses are easily accessed, trustworthy, relevant and an abundant source of CME for doctors . Examples of effective courses include an online curriculum for doctors to improve their knowledge, confidence and skills, about dietary supplements and distance learning to help doctors to raise their practice quality in tasks such as performing spirometry and evaluating asthma severity levels . Similar results were found in other studies .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Internet CME courses are easily accessed, trustworthy, relevant and an abundant source of CME for doctors . Examples of effective courses include an online curriculum for doctors to improve their knowledge, confidence and skills, about dietary supplements and distance learning to help doctors to raise their practice quality in tasks such as performing spirometry and evaluating asthma severity levels . Similar results were found in other studies .…”
Section: Discussionsupporting
confidence: 68%
“…The effectiveness of Internet CME has been investigated in several studies in high‐resource countries . Several studies have demonstrated that Internet‐based CME can improve FDs’ satisfaction, knowledge and practices; however, there have been few well‐designed studies with a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Os cursos possuem vídeos, fóruns de debates, entre outros recursos audiovisuais (37,53) . Gardiner et al (38) afirma que a educação online tem ganhado espaço por ser realizado de acordo com a preferência individual e fornece acesso a diversos recursos para ampliar o conhecimento.…”
Section: Discussionunclassified
“…Fricton et al (37) 2015 EUA Preventing chronic pain: a human systems approach-results from a massive open online course Online Learning Gardiner et al (38) 2015 EUA Online education for improving communication and documentation of dietary supplements among health professionals practicing in a hospital setting…”
Section: Online Learningmentioning
confidence: 99%